Internal architecture of mixed sand-and-gravel beach ridges : Miquelon-Langlade Barrier, NW Atlantic - Billy, Julie (CCSD, 2014)
The purpose of this PhD thesis was to define a complete and continuous sea-land-sea view of a paraglacial coastal barrier system, combining morphological and architectural approaches. Particularity of the Miquelon-Langlade isthmus (NO Atlantic) lies in its diversity and complexity of systems (spits, beach ridges, and lagoon) that fit together to form a composite barrier prograding along two open coasts. Investigations of this barrier included topographic (RTK-GPS), ground-penetrating radar (GPR) seismic, sedimentary (cores, augers, samples) and chronologic (OSL) data collections. This study of this paraglacial composite barrier make possible 1) to characterize all deposits of the paraglacial sequence (FSST, LST, TST, HST); 2) to emphasize the primary influence of islands geometry, bedrock and inherited topography on the coastal progradational pattern; 3) to provide a better understanding of the internal architecture of depositional processes and driving mechanisms of mixed sand-and-gravel beach ridges; 4) to examine the potential of these mixed beach-ridge systems to record and preserve paleo-sea-level information, to produce the first sea level trends for the Saint-Pierre-et-Miquelon archipelago over the last 3000 years. The combination of all these data provide a model of development of the barrier since the ice sheet retreat (13 700 yrs) to its present form, in a context of RSL rise and high local glaciogenic sediment supply, and a detailed view of the formation of the beach ridge plain over the last 3000 yrs. Cette thèse a pour objectif d’établir une vision globale et continue mer-terre-mer d’une barrière littorale paraglaciaire, en combinant une approche morphologique et architecturale. L’originalité de l’isthme de Miquelon-Langlade (NO Atlantique) entre les deux îles éponymes réside en sa diversité et complexité de systèmes (flèches, cordons littoraux, lagune) qui s’emboitent formant une barrière composite évoluant le long de deux façades ouvertes sur l’océan. Ce travail a été rendu possible grâce à ...